The RET proto-oncogene induces apoptosis: a novel mechanism for Hirschsprung disease - Bordeaux, Marie-Claire (Oxford University Press, 2000)
The RET (rearranged during transfection) proto-oncogene encodes a tyrosine kinase receptor involved in both multiple endocrine neoplasia type 2 (MEN 2), an inherited cancer syndrome, and Hirschsprung disease (HSCR), a developmental defect of enteric neurons. We report here that the expression of RET receptor induces apoptosis. This pro-apoptotic effect of RET is inhibited in the presence of its ligand glial cell line-derived neurotrophic factor (GDNF). Furthermore, we present evidence that RET induces apoptosis via its own cleavage by caspases, a phenomenon allowing the liberation/exposure of a pro-apoptotic domain of RET. In addition, we report that Hirschsprung-associated RET mutations impair GDNF control of RET pro-apoptotic activity. These results indicate that HSCR may result from apoptosis of RET-expressing enteric neuroblasts.